Effects of adding mannan oligosaccharides on digestibility and metabolism of nutrients, ruminal fermentation parameters, immunity, and antioxidant capacity of sheep. (29th January 2018) - Zheng, Chen; Li, Fadi; Hao, Zhengli; Liu, Ting
Abstract: The purpose of this study was to investigate the effects of adding mannan-oligosaccharides (MOS) on the following parameters in sheep: digestibility and retention rate of nutrients, ruminal fermentation, immunity, and antioxidant capacity. Twelve healthy crossbred wethers ( Suffolk ♂ × Small tail Han-yang ♀) with external ruminal fistula and similar body weights (28.04 ± 2.07 kg) were fed individually four treatments, three repeats of each treatment. The wethers diets were supplemental MOS at 0%, 1.2%, 1.6%, and 2.0%·kg −1 of basal diet (as fed basis). The experiment lasted 17 d, including 10 d of acclimation and 7 d of formal experimentation. The results showed that MOS did not influence the apparent digestibility and retention rate of nutrients, ruminal fermentation, and immunity or concentration of serum nitric oxide and activity of serum nitric oxide synthase ( P ≥ 0.07). However, the apparent digestibility of neutral detergent fiber and acid detergent fiber at MOS supplementation rates of 1.6% and 2.0% both tended to be greater than the control group ( P ≤ 0.103). There was also moderate evidence that MOS might increase the nitrogen retention rate ( P = 0.082). MOS increased the antioxidant ability of sheep ( P ≤ 0.018), especially at a dose of 1.6%: an increase in activity of total superoxide dismutase ( P = 0.007), glutathione peroxidase ( P = 0.018) and total antioxidant capacity ( P < 0.001), and a decrease in concentration of malondialdehyde ( P < 0.001) were found. The results indicated that in sheep MOS improved fiber digestion, N retention and some antioxidant abilities, but these effects may be too small to improve health and performance.